2011
DOI: 10.2478/v10019-011-0029-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of survival of patients receiving laparoscopic and open radical resection for stage II colon cancer

Abstract: BackgroundThe aim of the study was to compare the survival of patients receiving laparoscopic vs. open radical resection for stage II colon cancer.Patients and methodsTwo hundred and twenty patients with stage II colon cancer were enrolled from Beijing Chaoyang Hospital of Capital Medical University from January 2000 to December 2009, including 61 patients in the laparoscopic radical resection group and 159 patients in the open radical resection group. The survival data in both groups were compared using the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…There is now broad consensus that the laparoscopic approach is at least comparable to open surgery with respect to quality of resection and survival in colonic cancer . Similar to our findings, it was recently shown that laparoscopic surgery increases the chances of early adjuvant therapy .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…There is now broad consensus that the laparoscopic approach is at least comparable to open surgery with respect to quality of resection and survival in colonic cancer . Similar to our findings, it was recently shown that laparoscopic surgery increases the chances of early adjuvant therapy .…”
Section: Discussionsupporting
confidence: 89%
“…Time to referral to oncological treatment was median (interquartile range [i.q.r.]) 15 (12)(13)(14)(15)(16)(17)(18)(19)(20) days after surgery, time to first visit at the department of oncology was median (i.q.r) 27 (21-33) days, and adjuvant treatment was started a median (i.q.r.) of 2 weeks later-at 41 (34-50) days after surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] There is even some evidence that LCR result in better median overall survival for patients with stage II colon cancer, older than 75 years, when compared to open surgery. 4 Robotic surgical systems were designed to overcome the limitations of laparoscopic surgery, offering better visualization with three-dimensional magnified view and stable camera platform, stabilization of tremors and greater dexterity of movements. Moreover, they also improve the ergonom-ics, possibly reducing fatigue of the operating surgeon.…”
Section: Introductionmentioning
confidence: 99%
“…1 , 2 , 3 There is even some evidence that LCR result in better median overall survival for patients with stage II colon cancer, older than 75 years, when compared to open surgery. 4 …”
Section: Introductionmentioning
confidence: 99%